EFFECTIVENESS OF PJBL (PROJECT BASED LEARNING) BASED MICROTEACHING MODULES STUDENT LEARNING RESULTS ON BASIC TEACHING SKILLS MATERIAL - Fimansyah, Wira; Daud, Daud; Rulyani, Ayu; Br Maibang, Chintia Fani; Fatimah, Yusri Sajidah; Hasibuan, Alwy Syahri (STKIP Singkawang, 2023)
This study aims to test the module's effectiveness on student learning outcomes in microteaching courses. The type of research used is Pre-Experimental with a one-group pretest-posttest design. In this study, the treatment given was using teaching modules on essential teaching skills material. The research took place in the anthropology education study program, faculty of social sciences, State University of Medan. With research subjects totalling 30 students who received microteaching courses in the 2022/2023 academic year. Before getting the treatment, students were given a pretest, and after being given the treatment, a posttest was conducted with 50 questions in the form of objective or multiple-choice questions. The increase in learning outcomes was analyzed using the N-Gain formula. Based on the results of the N-Gain analysis, the average value was 0.41. There was an increase in student learning outcomes after using the microteaching module based on the PjBL (Project Learning) learning model on essential teaching skills material with a moderate category.